Computer-assisted three-dimensional surgical planning: 3D virtual articulator: technical note - Ghanai, Sassan; Marmulla, Rüdiger; Wiechnik, J.; Mühling, Joachim; Kotrikova, Bibiana (International journal of oral and maxillofacial surgery, 2010)
This study presents a computer-assisted planning system for dysgnathia treatment. It describes the process of information gathering using a virtual articulator and how the splints are constructed for orthognathic surgery. The deviation of the virtually planned splints is shown in six cases on the basis of conventionally planned cases. In all cases the plaster models were prepared and scanned using a 3D laser scanner. Successive lateral and posterior-anterior cephalometric images were used for reconstruction before surgery. By identifying specific points on the X-rays and marking them on the virtual models, it was possible to enhance the 2D images to create a realistic 3D environment and to perform virtual repositioning of the jaw. A hexapod was used to transfer the virtual planning to the real splints. Preliminary results showed that conventional repositioning could be replicated using the virtual articulator.
Gesehen am 03.03.2023